2018
DOI: 10.32861/jssr.spi6.213.216
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Spin off As a Breakthrough in Promoting Islamic Banking in Indonesia

Abstract: The Article 68 of Law No. 21 of 2008 on Sharia/Islamic Banking has stipulated the policy of UUS Splitting (Spinoff) to the Conventional Commercial Bank in Indonesia. This study aimed at determining the effectiveness of this policy based on Friedman’s theory of legal system. It is a juridical empirical research with data collection techniques including library research, interview and observation on BNI Syariah and Bukopin Syariah as banks that had been implemented spin off. According to Friedman, three factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition, the concept of SBC launched by the spin-off policy is indeed an ideal form of an Islamic bank (Yuspin & Nurwanti, 2020). However, even so, it turns out that the policy implementation is still ineffective (Yuspin & Fauzie, 2018).…”
Section: Islamic Bank Spin-off Study On Scopus Indexed Journalsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the concept of SBC launched by the spin-off policy is indeed an ideal form of an Islamic bank (Yuspin & Nurwanti, 2020). However, even so, it turns out that the policy implementation is still ineffective (Yuspin & Fauzie, 2018).…”
Section: Islamic Bank Spin-off Study On Scopus Indexed Journalsmentioning
confidence: 99%
“…In addition, a spin-off is deemed capable of increasing sharia compliance from Islamic banks in Indonesia (Rongiyati, 2016;Umam, 2010). However, implementing the Islamic bank spin-off policy is still ineffective (Yuspin & Fauzie, 2018). One of the highlights is the provision of spin-off regulations that require a minimum of 50% capital or assets from the parent bank, which is relatively difficult to fulfill (Rongiyati, 2016).…”
Section: Spin-off Policy In Islamic Banksmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is no international study on the topic of spin-off in the sharia insurance sector. Previous research on spin-off cases in the Islamic banking sector took the topic of financial performance, and the results showed that the financial performance of industries that has implemented the spin-off was found lower than that of Islamic banks that, in fact, have not implemented it (Al Arif, 2018; Kuncoro, 2018; Nurfadilah and Samidi, 2019; Nurkarima et al , 2021; Trinugroho et al , 2021; Al Arif et al , 2017; Yuspin and Fauzie, 2018).…”
mentioning
confidence: 96%